PENGARUH LEVERAGE, SALES GROWTH, FIRM SIZE, PROFITABILITAS DAN LIKUIDITAS TERHADAP FINANCIAL DISTRESS - Elviyo, Elviyo; Nugroho, Vidyarto (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to determine the effect of leverage, sales growth, firm size, profitability and liquidity on financial distress in mining companies listed on the Indonesia Stock Exchange in the 2017-2020 period. The sample selection was done by purposive sampling method so as to produce valid data as many as 18 companies. Data management in this study uses multiple regression analysis techniques assisted by Eviews 12 for Windows released 2020 and Microsoft Excel 2016. The results of this study state that firm size and liquidity have a significant influence on financial distress. The implication of this research is the need for a good mechanism in managing the company's debt so that the company avoids financial distress problems.